Facile preparation and conversion of 4,4,4-trifluorobut-2-yn-1-ones to aromatic and heteroaromatic compounds - Yamazaki, Takashi; Nakajima, Yoh; Iida, Minato; Kawasaki-Takasuka, Tomoko (Beilstein Journal of Organic Chemistry, 2021)
The concise preparation of 4,4,4-trifluorobut-2-yn-1-ones by the oxidation of the readily accessible corresponding propargylic alcohols as well as their utilization as Michael acceptors for the construction of aromatic and heteroaromatic compounds are reported.
Keywords: CF3-containing propargylic alcohols; CF3-containing ynones; oxidation; pyrimidines; salicylate derivatives

(untitled) - Inoue, M.; Sumii, Y.; Shibata, N. (ACS Omega, 2020)

(untitled) - Mei, H.; Han, J.; Fustero, S.; Medio‐Simon, M.; Sedgwick, D. M.; Santi, C.; Ruzziconi, R.; Soloshonok, V. A. (Chem. – Eur. J., 2019)

(untitled) - Wang, J.; Sánchez-Roselló, M.; Aceña, J. L.; del Pozo, C.; Sorochinsky, A. E.; Fustero, S.; Soloshonok, V. A.; Liu, H. (Chem. Rev., 2014)

(untitled) - Mizutani, K.; Yamazaki, T.; Kitazume, T. (J. Chem. Soc., Chem. Commun., 1995)

(untitled) - Yamazaki, T.; Mizutani, K.; Kitazume, T. (J. Org. Chem., 1995)

(untitled) - Miyagawa, A.; Naka, M.; Yamazaki, T.; Kawasaki-Takasuka, T. (Eur. J. Org. Chem., 2009)

(untitled) - Yamazaki, T.; Ichige, T.; Kitazume, T. (Org. Lett., 2004)

(untitled) - Yamazaki, T.; Yamamoto, T.; Ichihara, R. (J. Org. Chem., 2006)

(untitled) - Yamazaki, T.; Kawasaki-Takasuka, T.; Furuta, A.; Sakamoto, S. (Tetrahedron, 2009)

(untitled) - Watanabe, Y.; Yamazaki, T. (Synlett, 2009)

(untitled) - Watanabe, Y.; Yamazaki, T. (J. Fluorine Chem., 2010)

(untitled) - Watanabe, Y.; Yamazaki, T. (J. Org. Chem., 2011)

(untitled) - Yamazaki, T.; Watanabe, Y.; Yoshida, N.; Kawasaki-Takasuka, T. (Tetrahedron, 2012)

(untitled) - Ichikawa, T.; Kawasaki-Takasuka, T.; Yamada, S.; Yamazaki, T.; Kubota, T. (J. Fluorine Chem., 2013)

(untitled) - Shen, Y.; Xin, Y.; Cen, W.; Huang, Y. (Synthesis, 1984)

(untitled) - Bumgardner, C. L.; Bunch, J. E.; Whangbo, M. H. (J. Org. Chem., 1986)

(untitled) - Chechulin, P. I.; Filyakova, V. I.; Pashkevich, K. I. (Bull. Acad. Sci. USSR, Div. Chem. Sci. (Engl. Transl.), 1989)

(untitled) - Tajammal, S.; Tipping, A. E. (J. Fluorine Chem., 1990)

(untitled) - Brisdon, A. K.; Crossley, I. R. (Chem. Commun., 2002)

(untitled) - Wang, T.; Niu, D.; Hoye, T. R. (J. Am. Chem. Soc., 2016)

(untitled) - Murray, B. J.; Marsh, T. G. F.; Yufit, D. S.; Fox, M. A.; Harsanyi, A.; Boulton, L. T.; Sandford, G. (Eur. J. Org. Chem., 2020)

(untitled) - Ishihara, T.; Yamasaki, Y.; Ando, T. (Tetrahedron Lett., 1985)

(untitled) - Sibous, L.; Tipping, A. E. (J. Fluorine Chem., 1993)

(untitled) - Fouli, F. A.; Basyouni, M. N. (Acta Chim. Acad. Sci. Hung., 1981)

(untitled) - Shankar, R.; Jha, A. K.; Singh, U. S.; Hajela, K. (Tetrahedron Lett., 2006)

(untitled) - Ramachary, D. B.; Venkaiah, C.; Murali Krishna, P. (Chem. Commun., 2012)

(untitled) - Tong, W.; Li, Q.-Y.; Xu, Y.-L.; Wang, H.-S.; Chen, Y.-Y.; Pan, Y.-M. (Adv. Synth. Catal., 2017)

(untitled) - Yuan, Y.; Guo, Z.; Mu, Y.; Wang, Y.; Xu, M.; Li, Y. (Adv. Synth. Catal., 2020)

(untitled) - Ramasamy, M.; Lin, H.-C.; Kuo, S.-C.; Hsieh, M.-T. (Synlett, 2019)

(untitled) - Guan, H.-P.; Hu, C.-M. (J. Fluorine Chem., 1996)

(untitled) - Furuta, T.; Nakayama, M.; Suzuki, H.; Tajimi, H.; Inai, M.; Nukaya, H.; Wakimoto, T.; Kan, T. (Org. Lett., 2009)

(untitled) - Wang, X.-j.; Zhang, L.; Byrne, D.; Nummy, L.; Weber, D.; Krishnamurthy, D.; Yee, N.; Senanayake, C. H. (Org. Lett., 2014)

(untitled) - Matsuda, T.; Matsumoto, T. (Org. Biomol. Chem., 2016)

Fluorine in Heterocyclic Chemistry - Nenajdenko, V. G. (Springer, 2014)

(untitled) - Gupta, S.; Melanson, J. A.; Vaillancourt, L.; Nugent, W. A.; Tanoury, G. J.; Schatte, G.; Snieckus, V. (Org. Lett., 2018)

(untitled) - Geri, J. B.; Wade Wolfe, M. M.; Szymczak, N. K. (Angew. Chem., Int. Ed., 2018)

(untitled) - Romanov, A. R.; Rulev, A. Y.; Ushakov, I. A.; Muzalevskiy, V. M.; Nenajdenko, V. G. (Eur. J. Org. Chem., 2017)

(untitled) - Saijo, R.; Watanabe, G.; Kurihara, K.-i.; Kawase, M. (Heterocycles, 2014)

(untitled) - Liu, C.; Cui, Z.; Yan, X.; Qi, Z.; Ji, M.; Li, X. (Molecules, 2016)

(untitled) - Rawal, R. K.; Tripathi, R.; Katti, S. B.; Pannecouque, C.; De Clercq, E. (Bioorg. Med. Chem., 2007)

(untitled) - Funabiki, K.; Nakamura, H.; Matsui, M.; Shibata, K. (Synlett, 1999)

(untitled) - Jeong, I. H.; Jeon, S. L.; Kim, M. S.; Kim, B. T. (J. Fluorine Chem., 2004)